Better Living Through Chemistry? A Reply to Savulescu and Persson on 'Moral Enhancement'. (25th August 2013) - Sparrow, Robert
Abstract In 'Moral Enhancement, Freedom, and the God Machine', Savulescu and Persson argue that recent scientific findings suggest that there is a realistic prospect of achieving 'moral enhancement' and respond to Harris's criticism that this would threaten individual freedom and autonomy. I argue that although some pharmaceutical and neuro‐scientific interventions may influence behaviour and emotions in ways that we may be inclined to evaluate positively, describing this as 'moral enhancement' presupposes a particular, contested account, of what it is to act morally and implies that entirely familiar drugs such as alcohol, ecstasy, and marijuana are also capable of making people 'more moral'. Moreover, while Savulescu and Persson establish the theoretical possibility of using drugs to promote autonomy, the real threat posed to freedom by 'moral bioenhancement' is that the 'enhancers' will be wielding power over the 'enhanced'. Drawing on Pettit's notion of 'freedom as non‐domination', I argue that individuals may be rendered unfree even by a hypothetical technology such as Savulescu and Persson's 'God machine', which would only intervene if they chose to act immorally. While it is impossible to rule out the theoretical possibility that moral enhancement might be all‐things‐considered justified even where it did threaten freedom and autonomy, I argue that any technology for biomedical shaping of behaviour and dispositions is much more likely to be used for ill rather than good.